1996
DOI: 10.1001/archpsyc.1996.01830040039008
|View full text |Cite
|
Sign up to set email alerts
|

Recovery in Geriatric Depression

Abstract: These findings challenge the view that geriatric depression has a worse outcome than depression in younger adults. However, depressed patients with onset of first episode in late life may be at higher risk for chronicity. Antidepressant treatment prescribed by clinicians may decline prior to recovery despite evidence that high treatment intensity is effective in preventing relapse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
140
3
3

Year Published

1997
1997
2013
2013

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 224 publications
(155 citation statements)
references
References 38 publications
9
140
3
3
Order By: Relevance
“…This is supported by a study in severely depressed elderly patients, who rated their functionality as impaired whereas their clinicians did not. The authors concluded that the rating by experienced clinicians was able to distinguish disability contributing to depression from disability resulting from medical illness and/or cognitive impairment (28) . Another study reported that depressed elderly out-patients with chronic heart failure showed a tendency to underestimate their physical ability, whereas they had similar energy expenditure and walking ability as their non-depressive counterparts (27) .…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by a study in severely depressed elderly patients, who rated their functionality as impaired whereas their clinicians did not. The authors concluded that the rating by experienced clinicians was able to distinguish disability contributing to depression from disability resulting from medical illness and/or cognitive impairment (28) . Another study reported that depressed elderly out-patients with chronic heart failure showed a tendency to underestimate their physical ability, whereas they had similar energy expenditure and walking ability as their non-depressive counterparts (27) .…”
Section: Discussionmentioning
confidence: 99%
“…Although a trial of 8 weeks may be necessary to declare nonresponse in younger populations (Quitkin et al, 2003), longer studies may be necessary to detect adequately improvement in the elderly population. For elderly populations, a 12-week trial would allow a sufficient time for clinical response in most of this patient population (Cohn et al, 1990), including very old subjects (Gildengers et al, 2002) and elderly patients with comorbid illness who may require longer to respond (Alexopoulos et al, 1996). However, extending trial duration may increase the risk of placebo response (Walsh et al, 2002).…”
Section: Methodological Considerations For Antidepressant Trials In Tmentioning
confidence: 99%
“…LLD can be effectively treated using pharmacotherapy, psychotherapy or both, 21 and response and remission rates are comparable to those in individuals with mid-life depression. 22 Successful diagnosis and treatment of LLD improves depressive symptoms and decreases suicide rates.…”
Section: Late-life Depression: Definition Extent Burden and Hopementioning
confidence: 99%